Bentuk Pementasan Teater Daerah Sutradara Rusli Priaji Lakon Pusake Kujur Anjang-Anjang Kota Prabumulih - Kristiani, Septika; Syarifin, Ahmad (JPT : Jurnal Pendidikan Tematik, 2021)
This study aims to analyze the staging of a regional theater performance by director Rusli Priaji as Pusake Kujur Anjang-Anjang Kota Prabumulih. This research is a qualitative descriptive study with data collection techniques, namely observation, interviews and documentation. The object of this research is the idea of a Prabumulih City Regional Theater Performance with the play Pusake Kujur Anjang-Anjang, directed by Rusli Priaji. The subject of this research, the researcher tried to see from the staging and structure of the presentation of regional theater performances including the first characterization including character and fashion make-up, the two staging of plot including exposition, conflict, climax and resolution, sourced from field notes and Rusli Priaji as the director in this show. Researchers obtained data using observation, interview, and documentation techniques. The data obtained were analyzed using qualitative descriptive analysis by describing the state of the object in the field. The result of the research shows that this performance in his work tries to lift a legend from Prabumulih to make it into a play script. The staging of this performance Regional or traditional theater which is packaged in the staging of this modern theater can be seen from the packaging of the show.